Results from one and two implants compared with yearling cattle on summer pasture - Pruitt, R.; Fleck, A.; Smith, E.F.; Corah, L.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Reimplanting Ralgro in mid-July after implanting in late April did not improve daily summer gains compared to a single implant.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Implants; Yearling cattle